Pelatihan Pembuatan Kompos Berbasis Sampah Organik Rumah Tangga di Desa Kapur, Kabupaten Kubu Raya, Kalimantan Barat - Wahyu Setiyadi; Safriadi Safriadi; Amelia Arum Ramadhani; Mahmudi Mahmudi; Dermawati Sitorus; Sulistia Ningsih; Nadya Muliandari; Baaqy Amri Annisa; Alifiya Herwitarahman; Pustika Adwiyani (Universitas Maritim AMNI Semarang, 2024)
Improper waste handling is often the cause of environmental issues such as flooding and disease. Managing waste at the household level can significantly reduce environmental pollution. Currently, household organic waste is one of the largest contributors to overall waste. This activity aims to enhance housewives' skills and knowledge in composting household organic waste. It was conducted in Kapur Village, Kubu Raya Regency, West Kalimantan, with training sessions for housewives' associations. The activity included both presentations and hands-on composting practice. Participants' understanding was assessed through pre-test and post-test questionnaires. The results show that all participants understood the process and intended to apply composting practices in their households, positively contributing to waste reduction efforts.